2012
DOI: 10.1016/j.jinsphys.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Pre-adapted to the maritime Antarctic? – Rapid cold hardening of the midge, Eretmoptera murphyi

Abstract: During the 1960s, the midge, Eretmoptera murphyi, was transferred from sub-Antarctic South Georgia (55°S 37°W) where it is endemic to a single location on maritime Antarctic Signy Island (60°S 45°W). Its distribution has since expanded considerably, suggesting that it is pre-adapted to the more severe conditions further south. To test one aspect of the level of its pre-adaptation, the rapid cold hardening (RCH) response in this species was investigated. When juvenile (L1-L2) and mature (L3-L4) larvae of E. mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…However, larvae of B. antarctica are capable of undergoing RCH at subzero temperatures below the melting point of their body fluids (present study; Lee et al, 2006b;Teets et al, 2008). Similarly, in the subantarctic midge, Eretmoptera murphyi, the RCH response in supercooled larvae extends the lower limit of freeze tolerance (Everatt et al, 2012). In addition, other freeze-intolerant species of Antarctic arthropods, namely collembolans and mites, can swiftly increase their cold tolerance by decreasing their supercooling point antarctica.…”
Section: Discussion Rch At Subzero Temperaturesmentioning
confidence: 59%
See 1 more Smart Citation
“…However, larvae of B. antarctica are capable of undergoing RCH at subzero temperatures below the melting point of their body fluids (present study; Lee et al, 2006b;Teets et al, 2008). Similarly, in the subantarctic midge, Eretmoptera murphyi, the RCH response in supercooled larvae extends the lower limit of freeze tolerance (Everatt et al, 2012). In addition, other freeze-intolerant species of Antarctic arthropods, namely collembolans and mites, can swiftly increase their cold tolerance by decreasing their supercooling point antarctica.…”
Section: Discussion Rch At Subzero Temperaturesmentioning
confidence: 59%
“…In the present study, we demonstrated that RCH in frozen larvae could be induced at temperatures as low as -12°C, which is the lowest temperature known to induce the RCH response (Fig.2A). This ability of B. antarctica to undergo RCH while frozen differs from that of E. murphyi, in which only supercooled larvae exhibit the RCH response (Everatt et al, 2012). The lack of an RCH response in frozen larvae of E. murphyi suggests that internal ice formation inhibits the RCH response in this species (Everatt et al, 2012).…”
Section: Discussion Rch At Subzero Temperaturesmentioning
confidence: 92%
“…It is well known that faster cooling rates reduce 271 the survival of freeze-tolerant species, raise the SCP of freeze-avoiding species, and reduce the 272 capacity of these animals to respond to chilling injury (Sinclair et al 2003). RCH, the LLT of E. murphyi larvae decreased by up to 6.5 o C, and survival of larvae of the same 283 species was maintained above 80% for at least 22 h at the DT (Everatt et al 2012). 284 RCH also impacts on sub-lethal characteristics, including at temperatures above 0°C.…”
Section: Acclimation and Cooling Rates 256mentioning
confidence: 99%
“…Thus, physiological approaches must be guided by more detailed studies of current 792 microclimate conditions, and models forecasting rates of environmental change, to better predict 793 winners and losers under different climate scenarios. A greater threat to survival may in fact be 794 competition from newly colonising species -and investigating the physiological 'suitability' of 795 species whose distribution boundaries place them on the doorstep of polar environments is another 796 important research objective (Everatt et al 2012;Frenot et al 2005). 797…”
mentioning
confidence: 99%
“…It is possible that E. murphyi possesses similar physiological adaptations that underlie its high level of desiccation tolerance. Indeed, the capacity to which they respond to temperature is very similar (Lee et al 2006;Everatt et al 2012). …”
Section: Desiccation Tolerancementioning
confidence: 99%